The carbon cycle - Schimel, David Steven; Wigley, T. M. L. (Cambridge University Press, 2000)
Reducing carbon dioxide (CO2) emissions is imperative to stabilizing our future climate. Our ability to reduce these emissions combined with an understanding of how much fossil-fuel-derived CO2 the oceans and plants can absorb is central to mitigating climate change. In The Carbon Cycle, leading scientists examine how atmospheric carbon dioxide concentrations have changed in the past and how this may affect the concentrations in the future. They look at the carbon budget and the 'missing sink' for carbon dioxide. They offer approaches to modeling the carbon cycle, providing mathematical tools for predicting future levels of carbon dioxide. This comprehensive text incorporates findings from the recent IPCC reports. New insights, and a convergence of ideas and views across several disciplines make this book an important contribution to the global change literature. It will be an invaluable resource for students and researchers working in the field.